The Impact of the Politics of Privatization and Commercialization of Public Enterprises in Nigeria on the Level of Productivity and Economic Viability: The Case of Alscon and Nitel - Onuoha, Basil Chijioke; Umoh, Enoobong David; Ufomba, Henry (Asian Development Policy Review, 2017)
One of the most debated economic policies in the developing world today is the privatization and commercialization of public enterprises in Sub-Saharan Africa, and its positive and negative implications both in the short and long run. Much attention has been drawn to the observation that although privatization and commercialization was a popular policy in the liberalization process in developing economies in post cold war era, it has in many instances failed to translate to improved productivity and simulate the domestic economy (Obadan and Ayodele, 1988; Okanachi and Obutte, 2015). Situated within this observation, this paper opined that the interplay of politics and public policy direction of government in Nigeria have a negative influence on the process of privatization and commercialization of the state owned enterprises (SoEs) in the country in terms of their productivity, economic viability and contribution in stimulating the economy. Data for this study was drawn from 200 respondent (both managerial and non-managerial staffs) of the privatized Aluminums Smelter Company (ALSCON) and 200 too from Nigeria Telecommunication Limited (NITEL). Evidence showed that the two SoEs although marked for privatization and commercialization witnessed a downturn in their level of productivity and economic viability because the process was marred as a result of its politicization.